Touch medicine: bridging the gap between recent insights from touch research and clinical medicine and its special significance for the treatment of affective disorders - McGlone, Francis; Uvnäs Moberg, Kerstin; Norholt, Henrik; Eggart, Michael; Müller-Oerlinghausen, Bruno (Frontiers in Psychiatry, 2024)
Interpersonal touch represents the primal sensory experience between humans, fostering social bonding from the cradle to the death bed. In recent decades "affective touch" has been intensely studied, stimulated by the discovery of a population of mechanose nsitive unmyelinated C-tactile afferents in mammalian skin. A lack of touch in childhood is associated with negative consequences for psychosocial and physical health and the benefits of professional touch techniques in the prevention and treatment of various diseases have been shown over and over again in clinical studies. However, its application in mainstream clinical applications remains limited. To bridge the gap between recent discoveries in touch research and clinical medicine, we propose the establishment of a new discipline: 'Touch Medicine'. Here, we unfold the potential of Touch Medicine by focusing on the treatment of depression, which in our view is primarily a disorder of the lived body. Controlled studies and systematic reviews have demonstrated the antidepressant, anxiolytic and analgesic effects of specific massage techniques. Underlying mechanisms of action are currently under investigation, ranging from interoceptive, endocrinological, to stress-related or psychological underpinnings. Touch Medicine represents a novel interdisciplinary field connected to various medical specialities such as neonatology, paediatrics, pain medicine, neurology, psychiatry, and geriatrics -but also clinical psychology and psychosomatic medicine might benefit from the integration of these findings into their daily practice.